STUDY OF CELLULAR-HUMORAL IMMUNITY INDICATORS IN CHILDREN UNDER 18 YEARS OLD WITH ACUTE SUPPURATIVE OTITIS MEDIA AGAINST THE BACKGROUND OF CHRONIC HEPATITIS (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
One of the important problems of modern otolaryngology is the problem of hearing organ pathology in children with liver pathology. Occurring in early childhood against the background of chronic active hepatitis, acute suppurative otitis media (AGOS) often acquires a recurrent character and develops into a chronic form. This is due to the fact that the main immune system parameters in children with OGCS are disrupted at an early age.